2,4-Dinitrotoluene dioxygenase from Burkholderia sp. strain DNT: similarity to naphthalene dioxygenase. - Suen, W C (1996)
2,4-Dinitrotoluene (DNT) dioxygenase from Burkholderia sp. strain DNT catalyzes the initial oxidation of DNT to form 4-methyl-5-nitrocatechol (MNC) and nitrite. The displacement of the aromatic nitro group by dioxygenases has only recently been described, and nothing is known about the evolutionary origin of the enzyme systems that catalyze these reactions. We have shown previously that the gene encoding DNT dioxygenase is localized on a degradative plasmid within a 6.8-kb NsiI DNA fragment (W.-C. Suen and J. C. Spain, J. Bacteriol. 175:1831-1837, 1993). We describe here the sequence analysis and the substrate range of the enzyme system encoded by this fragment. Five open reading frames were identified, four of which have a high degree of similarity (59 to 78% identity) to the components of naphthalene dioxygenase (NDO) from Pseudomonas strains. The conserved amino acid residues within NDO that are involved in cofactor binding were also identified in the gene encoding DNT dioxygenase. An Escherichia coli clone that expressed DNT dioxygenase converted DNT to MNC and also converted naphthalene to (+)-cis-(1R,2S)-dihydroxy-1,2-dihydronaphthalene. In contrast, the E. coli clone that expressed NDO did not oxidize DNT. Furthermore, the enzyme systems exhibit similar broad substrate specificities and can oxidize such compounds as indole, indan, indene, phenetole, and acenaphthene. These results suggest that DNT dioxygenase and the NDO enzyme system share a common ancestor.